Gambaran Pengetahuan Ibu Hamil Tentang Tanda Dan Bahaya Kehamilan Di Wilayah Kerja Puskesmas Kabila Bone - Regita Pratiwi Thaib; Ni Made Dwi Santika Putri; Wahyudin N Hasan; ika wulansari; Nur Ayun R Yusuf; Cindy Puspita Sari Haji Jafar (Universitas Negeri Gorontalo, 2022)
Knowledge possessed by pregnant women is one of the factors that can affect the risk of dangers in pregnancy. The object of this research is a pregnant women at Kabila Bone Public Health Center, Bone Bolango Regency. This research aims to describe the knowledge of pregnant women about danger signs during pregnancy. The research’s method is a descriptive observational method, conducted from July to November 2021. The sample in this study is a pregnant women who came to check their pregnancy and met the research criteria and willing to fill out the quistionnaires. The sampling technique used an accidental sampling, as many as 30 samples obtained. From total of 30 pregnant women respondents, we obtained data on the knowledge of pregnant women who are willing to become respondents based on their characteristics. Most of the respondents are 20 -30 years old (86.7%), with high school aducation (56.7%), respondents with housewife occupation (90%), with 4 ANC visits (83.3%). Multi gravida (66.%), and respondents with birth spacing 2-5 years (40%). Result based on the research obtained from the majority of respondents showed that most of respondents had a good knowledge about pregnancy as many as 22 respondents(73.3%).